"Liquid‐Like" Surface Topography Waterborne Polyurethane Coatings with Bio‐Based and Easy‐Sliding Oil Repellency. Issue 7 (15th April 2022) - Hu, Jianfei; Huang, Wenjie; Wu, Yu; Zhao, Yuting; Wan, Ye; Meng, Yuan; Liang, Wangdong; Jiang, Tao; Zhang, Qunchao
Abstract: Herein, a "liquid‐like" surface topography and sustainable approach is reported to fabricate transparent oil‐repellent coatings, which involves fabricating new crosslinking polyols by siloxane oligomer modified castor oil fatty chain, followed to obtain waterborne polyurethane coatings. This surface morphology is formed by the grafted polydimethylsiloxane (PDMS) molecular chains in the coating molecules. This low surface tension and liquid‐like topography reduces the coefficient of friction with oily contaminants. Various low‐surface‐tension liquids can easily slide down the coating surfaces on substrates with lower tilting angle. The coatings are applicable to different substrates including glass, plastic, steel, and wood, and those with complex shapes and large surface areas. Thanks to the as‐described crosslinking structure of the coatings, their easy‐sliding oil repellency can be well maintained to avoid sand abrasion damages. Therefore, the advantageous characteristics of the as‐developed high transparency oil‐repellent and eco‐friendly coatings have the potential to replace traditional coatings and are highly practical for shielding against oily contaminants, chemical‐shield that protect coated plastics from dissolution by organic solvents, and nonstick coatings. Abstract : A "liquid‐like" surface topography and castor oil‐based transparent oil‐repellent coatings, which involves fabricating new crosslinking polyols by siloxane oligomer modified castor oil fatty chain, follow to obtain waterborne polyurethane coatings. The "liquid‐like" topography reduce the coefficient of friction with oily contaminants. This method provides a new idea for the preparation of biobased antifouling coatings.